2018
DOI: 10.3389/fendo.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Food-Derived Hemorphins Cross Intestinal and Blood–Brain Barriers In Vitro

Abstract: A qualitative study is presented, where the main question was whether food-derived hemorphins, i.e., originating from digested alimentary hemoglobin, could pass the intestinal barrier and/or the blood–brain barrier (BBB). Once absorbed, hemorphins are opioid receptor (OR) ligands that may interact with peripheral and central OR and have effects on food intake and energy balance regulation. LLVV-YPWT (LLVV-H4), LVV-H4, VV-H4, VV-YPWTQRF (VV-H7), and VV-H7 hemorphins that were previously identified in the 120 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Such sequences are inactive when present in the parental protein, but can be released after protein hydrolysis during gastro-intestinal digestion (GID), in vitro enzymatic hydrolysis, or microbial fermentation ( Korhonen and Pihlanto, 2006 ; Korhonen, 2009 ). The BAPs display interesting biological functions such as angiotensin converting enzyme (ACE) inhibition, mineral binding, antidiabetic, satiating, immunomodulating, opioid, antioxidant, or antimicrobial activities ( Nongonierma and FitzGerald, 2015 ; Park and Nam, 2015 ; Caron et al, 2017 ; Nielsen et al, 2017 ; Domenger et al, 2018 ). Research on BAPs provides insightful information on the impact of dietary proteins on health.…”
Section: Introductionmentioning
confidence: 99%
“…Such sequences are inactive when present in the parental protein, but can be released after protein hydrolysis during gastro-intestinal digestion (GID), in vitro enzymatic hydrolysis, or microbial fermentation ( Korhonen and Pihlanto, 2006 ; Korhonen, 2009 ). The BAPs display interesting biological functions such as angiotensin converting enzyme (ACE) inhibition, mineral binding, antidiabetic, satiating, immunomodulating, opioid, antioxidant, or antimicrobial activities ( Nongonierma and FitzGerald, 2015 ; Park and Nam, 2015 ; Caron et al, 2017 ; Nielsen et al, 2017 ; Domenger et al, 2018 ). Research on BAPs provides insightful information on the impact of dietary proteins on health.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that certain DPP-IV inhibitory peptides were able to cross the IB in vitro. Domenger et al showed that among five DPP-IV inhibitory peptides identified in a bovine hemoglobin intestinal digest, only three of them were recovered intact after the passage through a Caco-2 cells monolayer [ 44 , 56 ]. Lacroix et al, also evidenced the susceptibility of certain milk protein-derived DPP-IV inhibitory peptides to be cleaved by brush barrier peptidases [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dalziel et al found that whey protein concentrates decreased motility in the colon, while their corresponding hydrolyzates increased the frequency of contrations [ 25 ]. Domenger and coworkers reported that hemorphins, a group of opioid peptides encrypted in the beta-chain of hemoglobin, specifically, LLW-YPWT, LW-YPWT, W-YPWT, W-YPWTQRF, and YPWTQRF had effects on intestinal peristalsis, appetite, and food intake regulation [ 26 ].…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%